Perlindungan Hukum Terhadap Hak Konsumen E-Commers Dalam Perspektif Hukum Islam - Zainal Fanani (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
Technology information is currently a double-edged sword, because in addition to contributing to the improvement of welfare, progress and human civilization, as well as being an effective means of acts against the law, the focus of this research focuses on protecting consumer rights in e-commerce transactions and how the logical consequences are. for sellers and buyers in Islamic law to conclude that the legal protection of consumer rights in e-commerce, the right to get compensation, indemnity, and / or replacement, if the goods and / or services received are not in accordance with the agreement or not as it should be, Right to Get Advocacy, Protection and Efforts to Properly Settle Consumer Protection Disputes, Right to Correct, Clear, and Honest Information Regarding Conditions and Guarantee of Goods and/or Services, Right to Be Heard by Opinions and Complaints on Goods and/or Services Used, the right to choose goods and / or services as well as obtaining these goods and/or services in accordance with the exchange rate and conditions and guarantees promised, the right to comfort, security and safety in consuming goods and/or services, while in the perspective of Islamic law, emphasizes more on khiyar law in electronic transactions, various consumer rights are protected based on the Koran and al-Hadith